Coronal and Sagittal Plane Correction in Adolescent Idiopathic Scoliosis (AIS) using All Pedicle Screw versus Hybrid Instrumentation. A Systematic Review. Issue 1 (April 2016) - Mostafa, Wael; El-Sharkawi, Mohammad; Koptan, Wael; Darwish, Manal; Quraishi, Nasir A.
Introduction: Using all pedicle screw (APS) technique for the treatment of AIS is said to be more effective than hybrid instrumentation (HI). However this has not been proven yet. This systematic review on studies comparing all pedicle screw and hybrid instrumentation in the treatment of AIS tries to answer this question. Material and Methods: Pubmed and Medline Databases have been searched for articles from 1990 to June 2015 using the keywords "adolescent idiopathic scoliosis, " "hybrid" and "screw." Only papers with full text in English were reviewed. Eleven articles met the inclusion criteria (only adolescent idiopathic scoliosis, main thoracic and thoracolumbar curves, posterior instrumentation and fusion only i.e., no anterior release, at least 2 of the parameters evaluated is mentioned preoperative and at final follow up "one coronal plane parameter and one sagittal plane parameter"). Ten of the articles were retrospective cohort studies and one was a prospective cohort study. Level of evidence for all of them was 3. The following parameters were evaluated preoperative and at final follow up: thoracic kyphosis, main thoracic Cobb's angle, coronal correction ratio, global sagittal balance and global coronal balance. The follow up duration ranged from 2 – 5 years. Meta-analysis could not been performed because of the heterogeneity of the data. Results: The total number of patients was 614 (306 APS, 308 HI). The only significant difference found was the coronal correction ratio (67.71% in APS vs 58.34% in HI, p  = 0.001). Thoracic kyphosis changed from 24.5° to 21.3° in the APS group and from 25.4° to 23.6° in the HI group ( p  = 0.419). Global coronal balance changed from 15mm to 8.8mm in the APS group and from 14.6mm to 8.9mm in the HI Group ( p  = 0.811). Global Sagittal Balance changed from (−7)mm to (−4.6)mm in the APS and from (−1)mm to (−3.6)mm in the HI group ( p  = 0.344). Conclusion: Using all pedicle screw technique for the treatment of AIS may achieve better coronal plane correction. Contrary to the common belief, the use of Hybrid instrumentation does not lead to a better sagittal correction than all pedicle screw technique.